2(m+3)+3(m+4)=

Simple and best practice solution for 2(m+3)+3(m+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m+3)+3(m+4)= equation:


Simplifying
2(m + 3) + 3(m + 4) = 0

Reorder the terms:
2(3 + m) + 3(m + 4) = 0
(3 * 2 + m * 2) + 3(m + 4) = 0
(6 + 2m) + 3(m + 4) = 0

Reorder the terms:
6 + 2m + 3(4 + m) = 0
6 + 2m + (4 * 3 + m * 3) = 0
6 + 2m + (12 + 3m) = 0

Reorder the terms:
6 + 12 + 2m + 3m = 0

Combine like terms: 6 + 12 = 18
18 + 2m + 3m = 0

Combine like terms: 2m + 3m = 5m
18 + 5m = 0

Solving
18 + 5m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 5m = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 5m = 0 + -18
5m = 0 + -18

Combine like terms: 0 + -18 = -18
5m = -18

Divide each side by '5'.
m = -3.6

Simplifying
m = -3.6

See similar equations:

| ln(ln(x))=3 | | 10x-4+6-12x=8 | | 3(2x-5)=3(3-2) | | 3s^2+25s+42=0 | | 1+6n+-3=-14 | | 16x+13y=8 | | M*m-3m=18 | | -2x+3=-5x+6 | | 5y-9=8y-4y | | 9.7+x=11.24 | | 9x-5=2x+3 | | 4(5)+-20=0 | | 3x-2k=24x-16 | | 5x(x+12)=-180 | | 12.25+x=13.11 | | -2/p=4/11 | | 6x-84=3x-9 | | 3x(x+12)=2x(2x+4) | | -5+7x=3+9x | | n/5-5=7 | | -21z-33=30 | | 6x-4+6-2x=12 | | 5.2(2a-1)=7 | | 2h-12=2 | | -7x-24=312 | | 2x+40x= | | 4x-15(6-x)=-8(5-3x) | | -20p-5=-765 | | 77=5y-13 | | 16=4s-4 | | 9x+4.86=3x+12 | | 10x^2-50x-60=0 |

Equations solver categories